In Vitro Evaluation of the Antibacterial Effect of Virgin Coconut Oil Against Pseudomonas aeruginosa Associated with Folliculitis - Hati, Futi Kusuma; Rismaya, Rina; Aurellia, Dema Griseldis (Jurnal Riset Sains dan Kimia Terapan, 2025)
Virgin Coconut Oil (VCO) is a pure coconut oil rich in lauric acid, giving it potential antibacterial properties. Previous studies have successfully produced a VCO using a combined fermentation and enzymatic method with Neurospora sitophila, Lactobacillus plantarum, and papain. Nevertheless, further investigation is required to determine the antibacterial efficacy of the VCO against Pseudomonas aeruginosa, a bacterium responsible for folliculitis. This study analyzed of the antibacterial activity of VCO and Hydrolyzed Virgin Coconut Oil (HVCO) against P. aeruginosa in vitro. VCO is obtained by fermenting coconut milk using N. sitophila, L. plantarum and papain, then VCO undergoes hydrolysis with the aid of Lipozyme TL IM to yield HVCO. Inhibition zone assays were conducted to assess the antibacterial activity of 100% VCO and HVCO at varying concentrations of 25%, 50%, and 100%. The largest inhibition zone was shown by 100% HVCO (9.5 ± 0.3 mm in diameter), which was statistically significantly different from the control, ampicillin trihydrate. The data suggested that HVCO has enhanced antibacterial effectiveness against P. aeruginosa, compared to VCO. This increased activity is attributed to its higher free fatty acids and monolaurin content.